Brief Report: Evaluation of Inflammation and Atherogenesis Biomarkers Through 148 Weeks Postswitch to Dolutegravir and Rilpivirine in SWORD-1/SWORD-2. (1st September 2022) - Llibre, Josep M.; López Cortés, Luis Fernando; Aylott, Alicia; Wynne, Brian; Matthews, Jessica; Van Solingen-Ristea, Rodica; Vandermeulen, Kati; van Wyk, Jean; Kahl, Lesley P.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Switching to the 2-drug regimen dolutegravir + rilpivirine demonstrated noninferiority vs continuing a 3-drug or 4-drug current antiretroviral regimen (CAR) at week 48 and maintained high levels of virologic suppression to week 148 in the SWORD studies. We report inflammation and atherogenesis biomarkers postswitch to dolutegravir + rilpivirine. Setting: SWORD-1: 65 centers, 13 countries; SWORD-2: 60 centers, 11 countries. Methods: Virologically suppressed adults were randomized to switch to dolutegravir + rilpivirine (early-switch group; n = 513) or continue CAR (n = 511). Participants continuing CAR switched to dolutegravir + rilpivirine at week 52 (late-switch group; n = 477). Biomarkers were evaluated from Baseline to week 48 for dolutegravir + rilpivirine and CAR and noncomparatively for dolutegravir + rilpivirine postswitch through 148 weeks (early-switch) and 96 weeks (late-switch). Results: Through week 48, changes in biomarkers did not significantly differ between dolutegravir + rilpivirine and CAR groups, except for increases in soluble CD14 and decreases in fatty acid–binding protein-2, which favored dolutegravir + rilpivirine. For inflammation biomarkers through week 148, there was no marked change in C-reactive protein, inconsistent changes in soluble CD14 and interleukin-6, and increases in soluble CD163. For atherogenesis biomarkers through week 148, fatty acid–binding protein-2 and soluble vascular cell adhesion molecule-1 showed sustained reductions; D-dimer showed inconsistent increases between early-switch vs late-switch groups. Conclusions: No consistent pattern of change in biomarkers postswitch to dolutegravir + rilpivirine was observed through weeks 48 and 148 in SWORD-1/SWORD-2, suggesting no association of increased inflammation or atherogenesis with the 2-drug regimen while maintaining virologic suppression.